Tellurium and Mercury in Late Cretaceous to Early Eocene Sediments as Proxies for Volcanic Activity in the Deccan and North Atlantic Large Igneous Provinces - Nils Björn Baumann; Marcel Regelous; Thierry Adatte; Anette Regelous; Karsten M. Haase; Hassan Khozyem (Geochemistry, Geophysics, Geosystems)
Abstract Late Maastrichtian to Early Eocene sediments from Wadi Nukhul, Egypt were deposited between about 67 and 55.5 Ma during the eruption of the Deccan Traps and the North Atlantic Igneous Province (NAIP). We use Te and Hg as proxies for volcanism to constrain the timing of flood basalt volcanism relative to environmental perturbations and extinction events during this period. We find enrichment in Te in the latest Maastrichtian and earliest Danian and in the Late Paleocene to Early Eocene, which result from enhanced volcanic input of Te. An increase in volcanic Te during the Late Maastrichtian coincides with the Late Maastrichtian Warming Event. A second larger peak in Te begins about 120–80 kyr before the Cretaceous/Paleogene boundary (KPB) and continues into the Danian, with highest values about 70–30 kyr prior to the KPB, potentially related to eruptions of the voluminous Deccan Wai subgroup. The Chicxulub impact, therefore, did not trigger these eruptions, and Deccan volcanism likely led to climate instability, which may have amplified the environmental effects of the impact. A 6 Myr period of low Te during the Paleocene is followed by an increase in Te starting at 57.5 Ma and peaking at the Paleocene‐Eocene boundary (PEB; 56 Ma) during the opening of the North Atlantic and the highest eruptive rates of the NAIP. In contrast, Hg variations over the same time period are less systematic. Our results show that Te in sediments may be a robust proxy, complementary to Hg, for large volcanic events.